Analysis of E-Procurement Technology Implementation on Procurement Practices and Performance - Anantyo Pradana; Muhammad Asdar; Indrianty Sudirman (Hasanuddin Journal of Business Strategy, 2020)
Modern era as now, human life cannot be separated from dependence on a technology called the internet. The internet has mastered almost all aspects of human activities, ranging from sending letters, looking for information, and other activities. Especially in the field of business, this technology is very influential, as well as the procurement of goods and services has been done a lot online or commonly known as E-Procurement. This study aims to and analyzes the effect of E-Procurement technology on procurement performance, the effect of E-Procurement technology on procurement practices, and the effect of procurement practices on procurement performance. To implement these objectives the data collection techniques were used through questionnaires. The analysis technique used is path analysis and data evaluated in the first place using the classical assumption test (normality test, multicollinearity test, heteroscedasticity test, and linearity test). The results found that the use of e-procurement had a positive and significant effect on procurement performance and procurement practices at PT. Semen Tonasa in Pangkep Regency. Procurement practices have a positive and significant impact on procurement performance.